2009
DOI: 10.1124/jpet.109.159947
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine Receptor Stimulation of Mitochondrial Biogenesis

Abstract: Mitochondrial dysfunction is both a cause and target of reactive oxygen species during ischemia-reperfusion, drug, and toxicant injury. After injury, renal proximal tubular cells (RPTC) recover mitochondrial function by increasing the expression of the master regulator of mitochondrial biogenesis, peroxisomeproliferator-activated-receptor-␥-coactivator-1␣ (PGC-1␣). The goal of this study was to determine whether 5-hydroxytryptamine (5-HT) receptor agonists increase mitochondrial biogenesis and accelerate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 39 publications
2
66
0
Order By: Relevance
“…Activators of silent mating type information regulation 2 homolog 1 (SIRT1)-including isoflavones, resveratrol, and N-[2-[3-(piperazin-1-ylmethyl)imidazo[2,1-b][1,3]thiazol-6-yl]phenyl]quinoxaline-2-carboxamide (SRT1720) -have been demonstrated to induce PGC-1a and promote increased mitochondrial number and function (Rasbach and Schnellmann, 2008;Funk et al, 2010;Menzies et al, 2013). Our laboratory also identified the 5-hydroxytryptamine type 2 agonist, 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane hydrochloride (DOI), and the b 2 -adrenergic receptor agonist, formoterol, as potent inducers of PGC-1a and MB (Rasbach et al, 2010;Wills et al, 2012). Stimulation of MB after injury accelerates recovery of cellular morphology and function (Rasbach and Schnellmann, 2007;Funk et al, 2010;Rasbach et al, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…Activators of silent mating type information regulation 2 homolog 1 (SIRT1)-including isoflavones, resveratrol, and N-[2-[3-(piperazin-1-ylmethyl)imidazo[2,1-b][1,3]thiazol-6-yl]phenyl]quinoxaline-2-carboxamide (SRT1720) -have been demonstrated to induce PGC-1a and promote increased mitochondrial number and function (Rasbach and Schnellmann, 2008;Funk et al, 2010;Menzies et al, 2013). Our laboratory also identified the 5-hydroxytryptamine type 2 agonist, 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane hydrochloride (DOI), and the b 2 -adrenergic receptor agonist, formoterol, as potent inducers of PGC-1a and MB (Rasbach et al, 2010;Wills et al, 2012). Stimulation of MB after injury accelerates recovery of cellular morphology and function (Rasbach and Schnellmann, 2007;Funk et al, 2010;Rasbach et al, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…An early examination of the effects of a 5-HT 2 pan-agonist, DOI, revealed that it induced MB and promoted recovery of cellular respiration in RPTCs after acute oxidant injury (Rasbach et al, 2010). In this study, we sought to further define the role of the 5-HT 2 receptors in renal mitochondrial gene expression and oxidative metabolism.…”
Section: -Ht 2 Receptor Regulation Of Mitochondrial Genes Discussionmentioning
confidence: 99%
“…Primer sequences for 5-HT 2A , 5-HT 2B , and 5-HT 2C were previously described (Rasbach et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations